Analysis of solid waste management in the Northeast region of Brazil (Research, Society and Development, 2020)
This study aimed to analyze solid waste management in the Northeast region. For this, the deductive method was used and as methodological procedures, the literature review, analysis of data from the National Sanitation Research, state solid waste management plans and information regarding municipal plans provided by the Ministry of the Environment were employed. Environment. It was concluded that the main factors that impact waste management at the regional level are population growth, reduction of extreme poverty and consequent expansion of family income, increased purchasing power and low investment in waste management compared to other regions.